Epstein‐Barr virus and human papillomavirus serum antibodies define the viral status of nasopharyngeal carcinoma in a low endemic country. Issue 2 (24th April 2020) - Simon, Julia; Schroeder, Lea; Ingarfield, Kate; Diehl, Stefan; Werner, Jill; Brenner, Nicole; Liu, Zhiwei; Pawlita, Michael; Pring, Miranda; Butt, Julia; Ness, Andy; Waterboer, Tim
Abstract: Epstein‐Barr virus (EBV) causes nasopharyngeal carcinoma (NPC) in endemic regions, where almost every tumor is EBV‐positive. In Western populations, NPC is rare, and human papillomavirus infection (HPV) has been suggested as another viral cause. We validated multiplex serology with molecular tumor markers, to define EBV‐positive, HPV‐positive and EBV‐/HPV‐negative NPCs in the United Kingdom, and analyzed survival differences between those groups. Sera from NPC cases (n = 98) and age‐ and sex‐matched controls (n = 142) from the Head and Neck 5000 clinical cohort study were analyzed. IgA and IgG serum antibodies against 13 EBV antigens were measured and compared with EBER in situ hybridization (EBER‐ISH) data of 41 NPC tumors (29 EBER‐ISH positive, 12 negative). IgG antibodies to EBV LF2 correctly diagnosed EBV‐positive NPCs in 28 of 29 cases, while all EBER‐ISH negative NPCs were seronegative to LF2 IgG (specificity = 100%, sensitivity = 97%). HPV early antigen serology was compared to HPV molecular markers (p16 expression, HPV DNA and RNA) available for 41 NPCs (13 positive, 28 negative). Serology matched molecular HPV markers in all but one case (specificity = 100%, sensitivity = 92%). EBV and HPV infections were mutually exclusive. Overall, 67% of the analyzed NPCs were defined as EBV‐positive, 18% as HPV‐positive and 14% as EBV/HPV‐negative. There was no statistical evidence of a difference in survival between the three groups. These data provide evidence that both, EBV‐positive and HPV‐positive NPCs are present in a low incidence country, and that EBV and HPV serum antibodies correlate with the viral status of the tumor. Abstract : What's new? While Epstein‐Barr virus (EBV) causes almost all nasopharyngeal carcinoma (NPC) in endemic regions, human papillomavirus (HPV) may also cause NPCs in low‐incidence, Western populations. Here, the authors used molecular tumor markers to validate EBV and HPV multiplex serology to define the viral status of NPCs in the United Kingdom. IgG antibodies to the EBV antigen LF2 and HPV early antigen serology were highly specific and sensitive to identify EBV‐ and HPV‐positive NPCs, respectively. The results show that both EBV‐positive and HPV‐positive NPCs are present in a low‐incidence country, and that EBV and HPV serum antibodies correlate with the viral status of the tumor.